Risk factors for new-onset depression or anxiety following total joint arthroplasty: the role of chronic opioid use. Issue 11 (16th September 2019) - Wilson, Lauren; Bekeris, Janis; Fiasconaro, Megan; Liu, Jiabin; Poeran, Jashvant; Kim, David H; Gonzalez Della Valle, Alejandro; Memtsoudis, Stavros G
Abstract : Background: Several studies have evaluated the impact of preoperative depression on outcomes following total joint arthroplasty (TJA), however few have studied new-onset depression or anxiety after TJA. We aimed to identify the incidence of and risk factors for new-onset depression/anxiety after TJA, specifically focusing on the role of chronic opioid use. Methods: Patients who underwent total hip (THA) or total knee (TKA) arthroplasty from 2012 to 2015 were identified from the Truven MarketScan database. The main outcomes were new-onset depression or anxiety. The main risk factor of interest was chronic opioid use as a proxy for chronic pain; this was classified into three groups: isolated preoperative use, isolated postoperative use, and preoperative use that continued postoperatively. Multivariable logistic regression models were used to obtain ORs and 95% CIs. Results: Overall, 106 260 TJA procedures were included (34.3% THA/65.7% TKA); new-onset depression and anxiety were observed in 3.6% and 4.8% of patients, respectively. Preoperative chronic opioid use (6.3%; OR 1.88, 95% CI 1.47 to 2.40), isolated postoperative use (10%; OR 2.61, 95% CI 2.08 to 3.28), and continued postoperative use (7.8%; OR 2.08, 95% CI 1.74 to 2.49) were all associated with significantly increased odds of new-onset depression. Additional risk factors included female gender, younger age, comorbid psychological conditions, and hospital readmission within 6 months of surgery. Similar patterns were seen for new-onset anxiety. Discussion: Given the observed relationship between chronic opioid use and adverse psychological outcomes following TJA, the relationship between these two entities requires further evaluation, specifically to identify if there is a causal relationship.